kMucormicosys due to Saksenaea vasiformis in a dog - Reynaldi, Francisco José (2017)
A 2-year-old female Border collie was examined for dermatitis with a partial alopecic zone around her left front member. Six months later the lesion became swollen, alopecic with ulcerated areas. Microscopy analysis of samples showed numerous non-septate, branching, thin-walled and irregular shaped hyphal elements. Fungal cultures and molecular studies identified Saksenaea vasiformis. Treatments with griseofulvin, itraconazole and surgical debridement were used, however, fourteen months later the dog was euthanatized because of the unfavorable clinical outcome.